Elements of sustainability in Philippine forest governance an analysis of the community-based forest management and integrated forest management programs in Isabela, Quirino, Aurora, and Negros Oriental, Philippines - Bambalan, Gwendolyn C. 1961- (2005)
The evolution of forest administration in the Philippines clearly illustrates a discernible shift from state-centered management and regulatory to sustainable forest governance (SFG). The study borrowing from the definition of Asian Development Bank (ADB) uses the term SFG because it would like to emphasize that stakeholders' complementation and collaboration is an essential ingredient to the sustainability of forest governance programs such as Community-Based Forest Management (CBFM) and Integrated Forest Management (IFM). Managing the forest resources is one the country's commitment to the World Summit in Sustainable Development in 1992. However, in spite of the various programs implemented to ensure the sustainability of the forests, forestry problems still persist. The failure can be attributed to a confluence of factors: weak institutions, inadequate financial and logistical support, and poor program implementation. In the midst of various interpretations, definitions, and concepts on sustainable development, the Philippine forestry sector has yet to enhance its efforts towards generating a locally initiated understanding on SFG--its emerging concepts and views, elements and indicators which are crucial in defining the roadmap towards the sustainable governance of the country's forests. The study is a pioneering effort to clarify what constitutes and what are the elements of sustainable forest governance and will thus have significant contributions to the build up of literature, knowledge, undertanding and administration of forest programs in the Philippines. In the course of understanding SFG, it used the CBFM and IFM programs as benchmark cases, from which lessons and insights were derived. The case study was conducted in four (4) selected forestry projects located respectively in Quirino, Aurora, Isabela and Negros Oriental...